Strategi komunikasi Badan Pusat Statistik (BPS) Indonesia dalam mewujudkan “satu data perkebunan” - Pradhana, Chandra; Sumartias, Suwandi; Rahmat, Agus (Jurnal Praksis dan Dedikasi Sosial, 2025)
The communication strategy of Indonesia’s Central Bureau of Statistics (BPS) in realizing the “one plantation data” initiative This study aims to understand how the Communication Strategies of the Indonesian Central Statistics Agency (BPS) innovate to develop a data collection system for large companies under BPS’s responsibility. The informants in this research are Civil Servants from the Directorate of Statistics for Food Crops, Horticulture, and Plantations and representatives from plantation companies. The research uses a qualitative approach with a descriptive method. Theories applied include the Interpersonal Communication Theory by Joseph A. Devito and the Diffusion of Innovations Theory by Everett M. Rogers. The findings of this study indicate that the interpersonal communication strategies implemented, including openness, empathy, supportive attitudes, positive feelings, and equality, are vital in developing an innovative data collection system for large companies. The centralized diffusion communication model implies that the dissemination of innovation is carried out linearly from BPS to the relevant stakeholders through team coordination, involvement of plantation companies, the development of the Sedia Data Perkebunan Online system (SEDAPP Online), and training for operators from each company. Through SEDAPP Online, BPS can engage stakeholders actively in realizing "One Data for Plantations". It is hoped that BPS can apply this model to various future data collection activities across different sectors. Penelitian ini bertujuan untuk mengetahui bagaimana Strategi Komunikasi BPS dalam berinovasi untuk membangun sistem pengumpulan data perusahaan besar yang menjadi tanggung jawab BPS. Informan dalam penelitian ini adalah Apararatur Sipil negara (ASN) Direktorat Statistik Tanamaman Pangan, Hortikultura, dan Perkebunan, dan perwakilan perusahaan perkebunan. Metode penelitian ini adalah pendekatan kualitatif dengan metode deskriptif. Teori yang digunakan adalah Teori Komunikasi Interpersonal menurut Joseph A Devito dan Teori Difusi Inovasi milik Everett M Rogers. Hasil dari penelitian ini menemukan bahwa strategi komunikasi interpersonal yang diterapkan meliputi keterbukaan, empati, sikap mendukung, rasa positif, dan kesetaraan menjadi instrumen penting dalam membangun sebuah inovasi sistem pengumpulan data pada perusahaan besar. Model komunikasi sistem difusi tersentralisasi yang berarti penyebaran inovasi dilakukan secara linear dari BPS kepada stakeholder terkait melalui pelaksanaan koordinasi tim, pelibatan Perusahaan Perkebunan, Pembangunan system Sedia Data Perkebunan Online (SEDAPP Online), dan pelatihan terhadap operator dari masing-masing Perusahaan. Melalui SEDAPP Online BPS mampu untuk mengajak stakeholder berkontribusi aktif dalam mewujudkan “Satu Data Perkebunan”. Kedepan harapannya BPS mampu menerapkan model ini dalam berbagai kegiatan pengumpulan data pada berbagai sektor.